HYPOPLASTIC EFFECT OF PROSTOWIN VATI AND VASTIKARMA IN THE MANAGEMENT OF BENIGN PROSTATIC HYPERPLASIA - DR ARUN SINGH; DR AKHLESH KR. BHARGAVA; PROF. H.K. KUSHWAHA (Innovare Journal of Ayurvedic Sciences, 2013)
60 Patients were selected for the clinical study in 3 groups and 20 patients were in each group. The quality of life improved with the Prostowin Vati and Ksheerabala oil Vasti with the reduction in symptom score (IPSS and DPSS), Residual urine, Micturition time and improvement in Average flow rate. Old persons refuse operative treatment for their BPH symptoms and seeking a safe and effective treatment for easy life. In this situation the medicinal treatment may play an important role. Key words- Straining, Intermittency, International prostate symptom scoring system (IPSS), Danish Prostate Symptom scoring system (DPSS), Residual